Continuous selections via geodesics - Colombo, Giovanni; Goncharov, Vladimir V. (Topological Methods in Nonlinear Analysis, 2001)
Some continuous selection results for a class of nonconvex-valued maps are obtained. One of them contains Michael’s theorem, in the case of a Hilbert codomain. Methods of nonsmooth analysis and Γ-convergence are used.